Carbon quantum dot tailored counter electrode for 7.01%-rear efficiency in a bifacial dye-sensitized solar cell. Issue 71 (22nd August 2017) - Zhu, Wanlu; Zhao, Yuanyuan; Duan, Jialong; Duan, Yanyan; Tang, Qunwei; He, Benlin
Abstract : We present here a carbon quantum dot (CQD) tailored counter electrode (CE) for a bifacial dye-sensitized solar cell (DSSC). Abstract : We present here a carbon quantum dot (CQD) tailored counter electrode (CE) for a bifacial dye-sensitized solar cell (DSSC). Arising from wide spectral absorption, high optical transmission and the electron-enriched surface of the CE, the final bifacial DSSC device yields front and rear efficiencies of 9.08% and 7.01%, respectively.